Isolasi dan Karakterisasi Aktinomisetes Penghasil Antibakteri Enteropatogen Escherichia coli K1.1, Pseudomonas pseudomallei 02 05, dan Listeria monocytogenes 5407 - Dwi Ningsih Susilowati; Ratih Dewi Hastuti; Erny Yuniarti (Jurnal AgroBiogen, 2007)
Isolation and Characterization of Actinomycetes ProducingAntibacterial Compound into EnteropatogenikEscherichia coli K1.1, Pseudomonas pseudomallei 02 05and Listeria monocytogenes 5407. Dwi N. Susilowati,Ratih D. Hastuti, and Erny Yuniarti. The resistance ofbacterial pathogens to some antibacterial agents and sideeffects of the antibacterial usage demanded discovery ofnew effective, safe, and active antibacterial compounds.Some pathogenic bacteria, such as enteropathogen Escherichiacoli (EPEC) that cause diarrhoea on children andinfants, Pseudomonas pseudomallei that cause melioidosison human and animal, and Listeria monocytogenes thatcause listeriosis on newly born babies mortality and death ofpregnant woman. Actinomycetes is the largest bacterialgroup that produce antibiotics. More than 10,000 antibacterialcompounds had been discovered, two-third ofthem were produced by this bacterial group. A study wasdone to isolate and characterize Actinomycetes producingantibacterial compounds effective against EPEC K1.1 and P.pseudomallei 02 05. Soil samples were taken from 39locations in Indonesia and 115 actinomycetes isolates wereobtained. Two of the isolates, i.e., isolate A3.5 that waseffective against P. pseudomallei 02 05 and isolate F6.1 thatwas effective against EPEC K1.1 evaluated further. Theisolate A3.5 had an optimum time 72 hours to produce antibacterialcompound, while F6.1 took 96 hours. The antibacterialcompounds produced by both isolates were dissolvein the a 70% ethyl acetate solution, but not in a 40oCwarm methanol solution because it is very dissolved. Theantibacterial compound extracted from the isolate A3.5 hada similar effectiveness to antibiotics bacithracyn 10 unit andneomycin 30 g. On the other hand, the antibacterialcompound extracted from isolate F6.1 had a similar effectivenessto antibiotics colistin 10 g and doxyciclin 30 g.Further identification of the isolates suggested that both ofthem belongs to the genera Streptomyces.